2003
DOI: 10.1046/j.1365-2141.2003.04176.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble urokinase‐type plasminogen activator receptor (suPAR) as an independent factor predicting worse prognosis and extra‐bone marrow involvement in multiple myeloma patients

Abstract: Summary. The urokinase‐type plasminogen activator (uPA) system, which consists of a proteinase (uPA), a receptor (uPAR or CD87) and inhibitors, is involved in proteolysis, cell migration, tissue remodelling, angiogenesis and cell adhesion. Recent findings suggest that malignant plasma cells express uPA and uPAR. The expression of these factors could represent a process by which myeloma plasma cells interact with the bone marrow (BM) environment and influence important biological events such as bone matrix degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 34 publications
3
33
1
Order By: Relevance
“…Strikingly, in our study, uPAR antigen levels in serum of STS patients were found to be highly and significantly associated with poor OS in Kaplan -Meier analyses and in multivariate Cox's regression analyses. This is in line with other studies that reported that high serum levels of soluble uPAR (suPAR) were significantly associated with worse survival in colorectal, prostate, ovarian and breast cancer, as well as in multiple myeloma (Sier et al, 1998;Brünner et al, 1999;Miyake et al, 1999;Stephens et al, 1999;Riisbro et al, 2002;Rigolin et al, 2003;Shariat et al, 2007) In contrast to cell-bound uPAR, which focuses uPA mediated plasmin formation to the cell surface, the role and source of suPAR remain to be clarified . Holst-Hansen et al (1999) demonstrated that the amount of suPAR released from breast cancer cell lines was directly correlated to the number of viable cells.…”
Section: Discussionsupporting
confidence: 52%
“…Strikingly, in our study, uPAR antigen levels in serum of STS patients were found to be highly and significantly associated with poor OS in Kaplan -Meier analyses and in multivariate Cox's regression analyses. This is in line with other studies that reported that high serum levels of soluble uPAR (suPAR) were significantly associated with worse survival in colorectal, prostate, ovarian and breast cancer, as well as in multiple myeloma (Sier et al, 1998;Brünner et al, 1999;Miyake et al, 1999;Stephens et al, 1999;Riisbro et al, 2002;Rigolin et al, 2003;Shariat et al, 2007) In contrast to cell-bound uPAR, which focuses uPA mediated plasmin formation to the cell surface, the role and source of suPAR remain to be clarified . Holst-Hansen et al (1999) demonstrated that the amount of suPAR released from breast cancer cell lines was directly correlated to the number of viable cells.…”
Section: Discussionsupporting
confidence: 52%
“…Similarly, Rigolin et al [19] reported CD87 expression in all of their patients (n=49). On the other hand, Plesner et al [20] could not detect uPAR in any of their patients in a series including 10 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Rigolin et al [19] determined an association between high CD87 expression and lytic bone lesions. However, we could not demonstrate such a correlation in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations